AB0578 DIFFERENCES AND CHARACTERISTICS OF PRIMARY LARGE VESSEL VASCULTIS AND LARGE VESSEL VASCULITIS ASSOCIATED WITH GIANT CELL ARTERITIS. STUDY OF 28 CASES FROM THE SAME CENTER. (June 2019) - Calvo, I.; Ibarguengoitia, O.; Montero, D; Vega, L; María, L; Ruiz, M E.; Torre, I; Fernandez, O; Blanco, J M.; Inchaurbe, A R.; Pérez, Clara; Cuende, Eduardo; et al.
Abstract : Background: Large vessel vasculitis (LVV) is a severe entity with nonspecific clinical symptoms, which contributes to a delay in diagnosis and sometimes to serious complications. LVV can be primary or secondary, with giant cell arteritis (GCA) being the most common association. Objectives: To describe the characteristics and differences between patients with primary LVV and LVV associated with GCA in a single center. Methods: Retrospective study of patients with LVV in a University Hospital (January 2013-December 2018). Patients diagnosed with aortitis using an imaging test (PET-CT/angioCT/CT/MRI) were included. GCA was diagnosed by biopsy and/or ultrasound of the temporal artery. The primary LVV was considered by exclusion of inflammatory or infectious causes. Epidemiological, clinical and analytical variables, affected vascular territories and the treatment received in both groups were reviewed. Frequencies and percentages were used in qualitative variables, mean±SD in quantitative and for the comparison between groups Chi2 test or Fisher test was used in categorical variables and Student T test or U of Mann-Whitney in quantitative. The statistical analysis was performed with IBM SPSS v.23. Results: We included 28 patients diagnosed with LVV (9 between 2013-2015 and 19 between 2016-2018). 75% were female with an average age±SD of 71.18±10.8 years. They were divided into two groups: primary LVV (n=15) and LVV associated with GCA (n=13). The diagnosis of GCA was made by ultrasound (n=6), biopsy (n=5) and both tests (n=2). In 7 patients (54%) aortitis and GCA diagnosis was simultaneous. In LVV with GCA, headache was observed in 84.6% of patients and constitutional syndrome in 53.8%. Primary LVV was characterized by lower age at onset, inflammatory low back pain, fever, atypical polymyalgia rheumatica and lower CRP levels; only the first two variables reached statistical significance, probably due to sample size. TABLE 1 The mean number of affected vascular territories was 3 and thoracic aorta was the most affected territory in both groups. The steroid treatment was similar in both groups, whereas methotrexate (MTX) was used more frequently in the LVV associated with GCA. In the first 4 months, 1 patient with primary LVV required Tocilizumab (TCZ). The final clinical evolution was similar and favorable in both groups. At the last visit, after a mean follow-up of 11.94±8.5 months in the primary LVV and 29.63±14.8 months in the LVV secondary to GCA, 93% of patients were asymptomatic with a mean ESR of 24, 07±20 and CRP 0.56±0.91. Treatment used in primary LVV were: glucocorticoids (CS) (n=4), mean dose 8.75±7.4mg; MTX (n=11), mean dose 18.18±5.6mg/week and TCZ (n=2). In LVV associated with GCA, 2 patients were without treatment; CS (n=9), mean dose 4.75±4mg; MTX (n=8), mean dose 13.44±6mg/week and TCZ (n = 2). 15 imaging tests were performed 6-10 months after diagnosis. Later, after an average time of 28.77±10.7 months 9 more control PET-CT were requested. TABLE 2 . Conclusion: In this study, younger age at onset and inflammatory low back pain were more frequent in primary LVV with statistical significance. The most affected vascular territory was the thoracic aorta in both groups. The clinical and analytical evolution was similar in both populations. In the treatment, the only notable thing was the increased use of MTX in the LVV associated with GCA. 68% of the aortitis were diagnosed in the last 3 years due to greater clinical suspicion. PET-CT is a useful tool in the diagnosis of this pathology. Disclosure of Interests: None declared